Anti-Müllerian Hormone and Testicular Function in Prepubertal Boys With Cryptorchidism - Grinspon, Romina P.; Gottlieb, Silvia; Bedecarrás, Patricia; Rey, Rodolfo A. (Frontiers in Endocrinology, 2018)
Introduction: The functional capacity of the testes in prepubertal boys with cryptorchidism before treatment has received very little attention. The assessment of testicular function at diagnosis could be helpful in the understanding of the pathophysiology of cryptorchidism and in the evaluation of the effect of treatment. Anti-Müllerian hormone is a well-accepted Sertoli cell biomarker to evaluate testicular function during childhood without the need for stimulation tests. Objective: The aim of the study was to assess testicular function in prepubertal children with cryptorchidism before orchiopexy, by determining serum AMH. We also evaluated serum gonadotropins and testosterone and looked for associations between testicular function and the clinical characteristics of cryptorchidism. Materials and methods: We performed a retrospective, cross-sectional, analytical study at a tertiary pediatric public hospital. All clinical charts of patients admitted at the outpatient clinic and recorded in our database with the diagnosis of cryptorchidism, were eligible. The main outcome measure of the study was the serum concentration of AMH. Secondary outcome measures were serum LH, FSH and testosterone. For comparison, serum hormone levels from a normal population of 179 apparently normal prepubertal boys were used. Results: Out of 1557 patients eligible in our database, 186 with bilateral and 124 with unilateral cryptorchidism were selected using a randomization software. Median AMH SDS was below 0 in both the bilaterally and the unilaterally cryptorchid groups, indicating that testicular function was overall decreased in patients with cryptorchidism. Serum AMH was significantly lower in boys with bilateral cryptorchidism as compared to controls and unilaterally cryptorchid patients between 6 months and 1.9 years and between 2 and 8.9 years of age. The prevalence of serum AMH below the normal range detected between 9.5% and 36.5% of patients with hypogonadism according to the age group in bilaterally cryptorchid and between 6.3% and 16.7% in unilaterally cryptorchid boys. Testosterone and gonadotropin levels were less frequently outside the reference range. Conclusion: Prepubertal boys with cryptorchidism, especially those with bilaterally undescended gonads, have decreased AMH production. Although serum AMH may fall within the normal range, there is a considerable prevalence of testicular dysfunction during childhood in this frequent condition.